Study of direct CP violation in B-+/--> J/psi K-+/-(pi(+/-)) decays - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Amer Physical Soc, 2008)
We present a search for direct CP violation in B-+/- -> J/psi K-+/- (pi(+/-)) decays. The event sample is selected from 2: 8 fb(-1) of p (p) over bar collisions recorded by D0 experiment in run II of the Fermilab Tevatron Collider. The charge asymmetry A(CP)(B+ -> J/psi K+) = +0: 0075 +/- 0: 0061(stat) +/- 0: 0030 (syst) is obtained using a sample of approximately 40 000 B-+/- -> J/psi K-+/- decays. The achieved precision is of the same level as the expected deviation predicted by some extensions of the standard model. We also measured the charge asymmetry A(CP) (B+ -> J/psi pi(+)) = - 0: 09 +/- 0: 08(stat) +/- 0: 03(syst).